Політичне русинство на сучасному етапі - Мушинка, М. (Народна творчість та етнографія, 2009)
The author characterized the «political Rusyns’ movement» – a movement in Zakarpattia region of Ukraine and in neighbouring countries, analyses studies of main ideologists, considers the political Rusyns’ movement in Priashiv (Slovakia). Доповідь було зачитано на 26 конференції з української проблематики в Іллінойському університеті в Урбані-Шампейні 25 червня 2009 року.